IMPLEMENTASI SISTEM TRANSAKSI NON TUNAI DI DINAS LINGKUNGAN HIDUP KABUPATEN KEDIRI - Amandani, Yayang Erika; Solikah, Mar'atus; Widiawati, Hestin Sri (Universitas Nusantara PGRI Kediri, 2023)
Implementation of a non-cash transaction system is the government's effort to prevent corruption and misappropriation of funds. This is done in order to increase transparency in financial management at each agency in the region. This study aims to determine the process, advantages, and constraints of implementing a non-cash transaction system in financial management in the Kediri District Environmental Office. The approach taken is using a qualitative approach with a descriptive research type. Data was obtained from primary data and secondary data. In data collection procedures, this study used interview, observation, and documentation techniques. The validity of the findings uses source triangulation which aims to test the credibility of the data by checking data obtained from various sources. The conclusion of this study proves that the implementation of the system is still not in accordance with the theory and gradually towards a non-cash transaction system, while the implementation of a non-cash transaction system in regional expenditure is in accordance with the theory. The implementation of the non-cash transaction system at the Kediri Regency Environmental Service can be said to be quite good.